The Influence of Manpower Competence on Capital Investment Collection and their Implications on Performance (Case Study on MSMEs Assisted by the West Java Chamber of Commerce) - R Susanto Hendiarto; Fenna Tiara Rizky Maulany (Enrichment : Journal of Management, 2022)
The current problem is that performance is still far from expectations, while the accumulation of capital investment has not been encouraging, this is presumably because the competence of the workforce is still concerning. This study aims to determine the effect of workforce competence on the accumulation of capital investment and its implications for the performance of a case study on the West Java Chamber of Commerce and Industry fostered business in Bandung. The research method applied is in the form of a descriptive analytical survey method, while the sample used is 46 respondents. The variables studied from each respondent are workforce competence, capital investment accumulation, and performance. The type of data collected is primary data. The results of the study indicate that the competence of the workforce has no and no significant effect on the accumulation of capital investment. the accumulation of capital investment has no effect and is significant on performance. The implication is that the competence of the workforce needs to be applied programmatically and massively. The object of this research is the sample of respondents used is still limited to the business assisted by the West Java Chamber of Commerce in Bandung, therefore further research is necessary based on more varied sampling with a longer duration, in order to obtain generalizable results.